Analisis Framing Pemberitaan Bunuh Diri Di Media Dulohupa.id - Aridi, Maya; Sumarjo; thomas, Abdul wahab (JAMBURA JURNAL ILMU KOMUNIKASI, 2025)
Suicide reports in the mass media, especially in Gorontalo, are becoming an increasingly important issue. The media needs to be more attentive in reporting the escalation of suicide cases because it affects public perception and response. This study analyzed framing patterns in suicide reporting in the Dulohupa.id media for the January-June 2023 period. 14 of 22 suicide-related stories were selected to be analyzed using a descriptive qualitative approach. The methods applied included framing analysis based on the Zhongdang Pan and Gerald M. Kosicki models, which focused on four analytical structures: syntactic, scripted, thematic, and rhetorical. This approach examined how the media shapes public perception of a sensitive issue through word selection, narrative, and visual presentation. In addition, framing theory and social reality construction were used to explain how the media not only conveys information, but also influences the way people understand and respond to suicide issues. Based on the analysis, Dulohupa.id journalists tried to present news with sensitivity to social and emotional contexts, and avoid sensationalism to prioritize mental health issues as a trigger for suicide. With a close examination of word choice and in-depth narrative, Dulohupa.id contributed to a more objective understanding and increased public awareness of the importance of suicide prevention.